2011
DOI: 10.1101/cshperspect.a009803
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Techniques to Study Lipid Dynamics

Abstract: Biological research has always tremendously benefited from the development of key methodology. In fact, it was the advent of microscopy that shaped our understanding of cells as the fundamental units of life. Microscopic techniques are still central to the elucidation of biological units and processes, but equally important are methods that allow access to the dimension of time, to investigate the dynamics of molecular functions and interactions. Here, fluorescence spectroscopy with its sensitivity to access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 238 publications
(221 reference statements)
0
73
1
Order By: Relevance
“…The concept of sphingolipid-sterol-protein rafts that were smaller than the resolution of the optical microscope stimulated the search for novel methodologies. Recent studies using different imaging and spectroscopic methods have revealed interesting glimpses of how the lipids and proteins behave in the crowded bilayer (Sezgin and Schwille 2011). These studies have confirmed the existence of cholesteroldependent nanoscale assemblies of sphingolipids and GPI-anchored proteins in the plasma membrane of living cells.…”
Section: The Dynamic Organization Of the Plasma Membranementioning
confidence: 58%
“…The concept of sphingolipid-sterol-protein rafts that were smaller than the resolution of the optical microscope stimulated the search for novel methodologies. Recent studies using different imaging and spectroscopic methods have revealed interesting glimpses of how the lipids and proteins behave in the crowded bilayer (Sezgin and Schwille 2011). These studies have confirmed the existence of cholesteroldependent nanoscale assemblies of sphingolipids and GPI-anchored proteins in the plasma membrane of living cells.…”
Section: The Dynamic Organization Of the Plasma Membranementioning
confidence: 58%
“…Although confocal microscopy studies have reported co-localization of certain molecules with putative lipid raft markers (such as cholera toxin) as evidence of their raft association 44 , in general the resolution of such systems is insufficient to directly assay raft domain structure and composition. To overcome this limitation, several optical tools have recently been developed 45,46 and applied to investigate nano-scale structures and dynamics in cells. For instance, super-resolution optical microscopy approaches such as photoactivated localization microscopy (PALM), stimulated emission depletion (STED) microscopy (Supplementary Box S2), and near-field scanning optical microscopy (NSOM) have been used to visualize lipid-mediated protein clustering 4750 .…”
Section: Studying Lipid Raftsmentioning
confidence: 99%
“…Figure 2B compares values of the partitioning coeffi cient %Lo for the different Chol analogs. Due to the compositional complexity, the molecular Here, d ( P STED ) and D ( P STED ) are the diameter of the observation spot and the average transit time at the STED power, P STED , and d ( P STED = 0) and D ( P STED = 0) the respective parameters at confocal recordings, where the diameter of the confocal spot [ d ( P STED = 0) = 200 nm for 488 nm and 240 nm for 635 nm excitation] has been determined from imaging fl uorescent beads or from theory ( 36 ). Shortening of the transit time D due to photobleaching from the STED laser is unlikely, as has been shown by several control measurements before, i.e., the decrease in d with STED power P STED is not a result of photobleaching by the STED laser [e.g., ( 37,38 )].…”
Section: Colocalization Analysismentioning
confidence: 99%